Genetic Progress for Yield and Yield Components and Reaction to bean Anthracnose (Colletotrichum lindemuthianum) of Medium Sized Food Type Common Bean (Phaseolus Vulgaries L.) in West Shoa Zone, in Ethiopia - Solomon Bekele; Firew Mekbib; Gemechu Keneni; Birhanu Amsalu (Open Journal of Plant Science - Peertechz Publications, 2022)
Eleven common bean (Phaseolus Vulgaris L.) varieties that were released in Ethiopia from 1998 to 2014 were evaluated as medium seeded food type common bean varieties. The objectives of this study were to: (1) estimate the genetic progress made in 16 years of common bean breeding in Ethiopia; (2) assess changes in associated traits in the genetic improvement of common bean varieties released in Ethiopia; and (3) assess the reaction of common bean varieties to bean anthracnose [Clletotrichum lindemuthianum (Sacc. & Magnus) Briosi & Cavara]. The study was conducted at two locations, Bako and Gute during the 2014/2015 cropping season in a randomized complete block design (RCBD) with three replications. Days to 50% flowering (DF), Days to 90% maturity (DM), Grain filling period (GFP), Hundred Seed weight (HSW), Biomass yield (BMY), Grain yield per plot (GY), Harvest index (HI), Biomass production rate (kg/ha/day), Seed growth rate (kg/ha/day), Grain yield per day (kg/ha/day) and Anthracnose (1-9) scale data were collected on plot basis and Plant height, Number of pods per plant, Number of seeds per pod, Number of seeds per plant and grain yield per plant data's were collected on a plant basis. Combined analysis of variance showed highly significant differences among the common bean varieties and between test environments for hundred seed weight. The variety by location (VXL) interaction showed highly significant differences in biomass yield, harvest index, days to flowering, grain filling period, and biomass production rate. Regression analysis of mean performance at both environments on year of varietal release showed positive relationship for Gran yield (r = 0.08), Seed weight (r = 0.08) and Harvest index (r = 0.4) but negative relationship for Biomass yield (r = 0.04) and anthracnose disease severity (r = 0.016). The highest mean grain yield was 3008.7 kg ha-1 for the Haramaya variety and the lowest was 1708.8 kg ha-1 for Ada, with an overall mean of 2271.1 kg ha-1. The annual rate of genetic progress was 22.3 kg ha-1 (0.31% ha-1), 0.56g 100 seeds-1 year-1, 0.006%, 0.19%, and -60 kg ha-1 year-1 for grain yield, seed weight, harvest index, anthracnose disease severity, and biomass yield respectively. Generally, grain yield was slightly increased in the period of genetic improvement. Grain yield day-1 (90%) character explained more for the variation of grain yield but, anthracnose disease severity played the major role as grain yield did not respond significantly increment by (-33%) than seed weight (-0.01%) from stepwise regression results. The yield of medium seeded food type common bean varieties was increased due to grain yield day-1 for the past sixteen years (1998-2014) of breeding. The future crucial consideration will be managing the disease, like anthracnose disease for this common bean class and finally, Haramaya (3008.7 kg ha-1), SER- 125 (2954.8 kg ha-1), and SER-119 (2653.1 kg ha-1) will be recommended for the study area.